Exploring the role of community engagement in improving the health of disadvantaged populations: a systematic review - Cyril, Sheila (Glob Health Action, 2015)
BACKGROUND: Although community engagement (CE) is widely used in health promotion, components of CE models associated with improved health are poorly understood. This study aimed to examine the magnitude of the impact of CE on health and health inequalities among disadvantaged populations, which methodological approaches maximise the effectiveness of CE, and components of CE that are acceptable, feasible, and effective when used among disadvantaged populations. DESIGN: The systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We carried out methodological assessments of the included studies using rating scales. The analysis focussed on model synthesis to identify the key CE components linked to positive study outcomes and comparative analysis between positive study outcomes, processes, and quality indicators of CE. RESULTS: Out of 24 studies that met our inclusion criteria, 21 (87.5%) had positively impacted health behaviours, public health planning, health service access, health literacy, and a range of health outcomes. More than half of the studies (58%) were of good quality, whereas 71% and 42% of studies showed good community involvement in research and achieved high levels of CE, respectively. Key CE components that affected health outcomes included real power-sharing, collaborative partnerships, bidirectional learning, incorporating the voice and agency of beneficiary communities in research protocol, and using bicultural health workers for intervention delivery. CONCLUSIONS: The findings suggest that CE models can lead to improved health and health behaviours among disadvantaged populations if designed properly and implemented through effective community consultation and participation. We also found several gaps in the current measurement of CE in health intervention studies, which suggests the importance of developing innovative approaches to measure CE impact on health outcomes in a more rigorous way.